Validation of the polycystic ovary syndrome health-related quality of life questionnaire (PCOSQ) in the clinical community in our gynaecological endocrine clinic - Ncube, Nkosinathi (Department of Obstetrics and Gynaecology, 2017)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age and impacts negatively on their health related quality of life (HRQoL). The Polycystic Ovary Syndrome Questionnaire (PCOSQ) is a disease specific questionnaire used to measure HRQOL in affected women. This questionnaire has not been validated for use in the clinical population of South Africa. This study aimed to assess the psychometric properties of the PCOSQ in our population and to compare findings with those from the WHOQOL-BREF, a generic questionnaire that measures HRQoL. Methods: This was a cross sectional analytical study of women with PCOS as defined by the Rotterdam criteria attending the Gynaecological Endocrine Clinic at Groote Schuur Hospital in Cape Town. The PCOSQ and WHOQOL-BREF were administered at the first interview and a repeat PCOSQ interview was conducted telephonically within a period of 2 to 7 days. The clinical data of the participants at initial diagnosis were obtained from the clinical records. Results: A total of 105 consenting women were recruited over a period of 8 months from November 2013 to July 2014. Sixty-seven participants responded to the second follow up interview for test-retest reliability. The test-retest reliability was good with intra-class correlation coefficients from all domains being above 0.8 (0.820-0.929, P<0.001). The Cronbach's alpha coefficients of internal consistency were above 0.7 in all domains with the exception of the menstrual domain, which scored 0.65. Construct validity was demonstrated by a statistically significant correlation between the corresponding domains of the WHOQOLBREF (P<0.05). Secondary factor analysis confirmed the domain structure of the PCOSQ. The scores from all domains were reflective of an impaired quality of life. Weight had the most impact on the HRQoL. The WHOQOL-BREF demonstrated a poor internal consistency in the study population. Conclusions: The PCOSQ is a valid questionnaire for measuring the HRQoL in our clinical population and is preferred above the WHOQOL-BREF. The incorporation of the domain on acne and further exploration of the domain of menstrual problems could be undertaken to strengthen its factor structure. PCOS has an adverse effect on the HRQoL. Weight has the biggest impact on the HRQoL. The WHOQOL-BREF is suboptimal in measuring HRQoL in women with PCOS, as it is not specific to the condition.